Glycoproteomics analysis of complement factor H and its complement-regulatory function during Streptococcus pneumoniae-associated hemolytic uremic syndrome - Baas, Laura M.; Wijnsma, Kioa L.; Zijlstra, Fokje; van de Kar, Nicole C. A. J.; ter Steeg, Lieke; Bouts, Antonia H. M.; Michels, Marloes A. H. M.; Langereis, Jeroen D.; Lefeber, Dirk; Wessels, Hans J. C. T.; van den Heuvel, Lambertus P. (Frontiers in Immunology, 2025)
Hemolytic uremic syndrome caused by an invasive Streptococcus pneumoniae infection (SP-HUS) is a rare and severe disease that primarily affects children under two years of age. The pathophysiology of SP-HUS remains poorly understood, and treatment is largely supportive. Complement factor H (FH) is a key regulator of the alternative pathway of the complement system. It has been hypothesized that loss of sialic acids from FH’s N-glycans may impair its regulatory functions, thereby potentially leading to complement-mediated endothelial cell damage in SP-HUS. In this study, we investigated the N-glycosylation patterns of FH across three N-glycosylation sites for four SP-HUS patients and compared it to healthy controls using LC-MS/MS-based glycopeptide profiling. We identified significant changes in FH glycosylation during the acute phase of SP-HUS, including an increased presence of N-glycans lacking sialic acids, galactose and N-acetylglucosamine (GlcNAc) relative to the controls. This abnormal glycosylation was most prominent during the acute phase in all patients and showed partial or complete normalization during remission. Interestingly, despite these major glycosylation changes, functional assays revealed no significant impairment in the complement regulatory activity of FH, as measured by its ability to facilitate C3b degradation and to prevent complement-mediated hemolysis of sheep erythrocytes. In conclusion, our findings show that FH’s N-glycosylation is severely altered in the acute phase in SP-HUS patients, comprising more than just the loss of sialic acids. However, these changes do not directly affect FH’s complement regulatory function. These results highlight the complex yet poorly understood role of N-glycosylation during infection, and the contribution of FH’s N-glycans to complement (dys)regulation and disease pathogenesis.